STRES KERJA PADA DEWASA AWAL YANG BEKERJA DI DESA JATILOR - Nopiyanti, Pipit; Septiara, Mamtha Shielfa; Pramoni, Novita Budi; Patria, Helvetia Fajar (SENTRI: Jurnal Riset Ilmiah, 2024)
This study aims to obtain an overview of work stress in early adulthood who work in Desa Jatilor, Kecamatan Godong, Kabupaten Grobogan, Jawa Tengah. The method used in this research is a qualitative method with data collection techniques through interviews. Data collection involved 7 people with early adulthood who were working and came from Desa Jatilor, Kecamatan Godong, Kabupaten Grobogan, Jawa Tengah. The results showed that all subjects almost experienced the same response when experiencing work stress. Like their heart beats fast and their emotions become unstable. And responses that are not experienced by all subjects such as not reducing interactions with people, not delaying doing work, and the relationship of all subjects with subject friends does not establish when the worm experiences work stress